2022
DOI: 10.1155/2022/8695196
|View full text |Cite
|
Sign up to set email alerts
|

qHBsAg for the Identification of Liver Histological Abnormalities in HBeAg-Negative Chronic Hepatitis B Patients with Normal and Mildly Elevated ALT Levels

Abstract: Backgrounds. Noninvasive detection of histological abnormalities remains challenging in patients with HBeAg-negative chronic HBV infection with normal or mildly elevated levels of alanine aminotransferase (ALT). This study aimed to assess the utility of serum quantitative hepatitis B surface antigen (qHBsAg) in identifying significant histological lesions in this population. Methods. This is a single-center study with retrospective analysis of 392 treatment-naive patients of HBeAg-negative chronic HBV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The AUROC of the API was 0.789, if API is higher than 0.519, antiviral therapy is considered to be recommend. Previous report has found that AST was better than ALT in predicting liver in ammation and brosis [22][23][24], similar to the results of our study. It is partly because the clarity of AST correlates with ALT level [25], or partly related to injury of mitochondrial with advanced brosis [26,27].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The AUROC of the API was 0.789, if API is higher than 0.519, antiviral therapy is considered to be recommend. Previous report has found that AST was better than ALT in predicting liver in ammation and brosis [22][23][24], similar to the results of our study. It is partly because the clarity of AST correlates with ALT level [25], or partly related to injury of mitochondrial with advanced brosis [26,27].…”
Section: Discussionsupporting
confidence: 93%
“…platelet destruction the accumulation and destruction of platelets in hypertensive splenomegaly, and as brosis progresses, hepatic production of thrombopoietin decreases [33].This study showed that HBsAg level was an independent virological marker to evaluate the signi cant brosis. In our study,the median log 10 HBsAg was consistent with previous study [24], we used the median log 10 HBsAg level to divided patients into high and low HBsAg groups. In our study, we discovered that signi cant brosis was more serious observe in high HBsAg group than that in low HBsAg group.The log 10 HBsAg level in S ≥ 2 group was signi cantly higher than that in S 2 group.…”
mentioning
confidence: 58%
“…Among the 23 studies (6 prospective studies 24–30 and 17 retrospective studies 31–47 ), patients were mainly from Asia (15 studies from China), middle age (mean age range: 26.8–45.2 years old), and more male participants (median male percentage: 64%) (Table 1). The studies used several scoring systems for liver pathology, including 10 studies that used Scheuer's method, six that used METAVIR, and five that used Ishak.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 684 articles were selected for full-text review, and finally, 23 studies comprising 4010 patients were included (Figure 1). Among the 23 studies (6 prospective studies [24][25][26][27][28][29][30] and 17 retrospective studies [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] ), patients were mainly from Asia (15 studies from China), middle age (mean age range: 26.8-45.2 years old), and more male participants (median male percentage: 64%) (Table 1). The studies used several scoring systems for liver pathology, including 10 studies that used Scheuer's method, six that used METAVIR, and five that used Ishak.…”
Section: Characteristics Of Studies Includedmentioning
confidence: 99%